First report comparing the two types of single-incision robotic sacrocolpopexy: Single site using the da Vinci Xi or Si system and single port using the da Vinci SP system - Sa Ra Lee; A-mi Roh; Kyungah Jeong; Sung Hoon Kim; Hee Dong Chae; Hye-sung Moon (Elsevier, 2021)
Objective: The gold standard procedure for treating patients with apical pelvic organ prolapse (POP) is sacrocolpopexy. However, no report comparing the two types of single-incision robotic sacrocolpopexy, namely, single-site robotic sacrocolpopexy (SS-RSC) and single-port robotic sacrocolpopexy (SP-RSC) exists. Therefore, we compared the safety and effectiveness of SS-RSC and SP-RSC. Materials and methods: In this study, 48 patients who underwent single-incision RSC, 40 non-consecutive patients who underwent SS-RSC, and 8 consecutive patients who underwent SP-RSC for symptomatic POP quantification stage III-IV and were eligible for the 1-year follow-up (FU) were included. We compared the surgical time and operative outcomes of SS-RSC and SP-RSC. We also compared the data of the initial 8 cases in each group. Results: The mean patient age was 59.2 ± 11.0 years and 66.1 ± 8.0 years in the SS-RSC (n = 40) and SP-RSC (n = 8) groups, respectively. The mean operative time (OT) and console time were comparable between the SS-RSC and SP-RSC groups (135.3 ± 31.6 min vs 141.8 ± 23.5 min; 94.6 ± 32.2 min vs 89 ± 9.5 min, respectively). The docking time and cervix suturing time were short in the SP-RSC group (P < 0.05). However, in the analysis of the initial 8 cases in each group, all surgical times except the cervix suturing time were shorter in the SP-RSC group (P < 0.05). Three cases had intraoperative bladder injury (two [5.0%] in the SS-RSC and one [12.5%] in the SP-RSC group). Two cases (5.0%) had umbilical incisional hernia in the SS-RSC group. Two cases had vaginal mesh erosion on the posterior vaginal wall, with 1 case in each group. One case (2.5%) experienced a recurrence of POP; an anterior compartment POP-Q stage 2 following SS-RSC at the 4-week FU. Conclusion: Single-incision RSC, both SS-RSC and SP-RSC, is a feasible and effective surgical option for treating symptomatic apical POP with an aesthetic finish.